ORGANIZATIONAL DYNAMIC : THE ROLE OF PERCEIVED SUPPORT, EMPLOYEE ENGAGEMENT, COMMITMENT AND PROFESSIONALISM ON PERFORMANCE - Wiranti, Elza Devi; Darmawan, Akhmad; Muji Rahayu, Tri Septin; Haryanto, Totok (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
This study aims to analyze the effect of perceived organizational support, employee engagement, organizational commitment and professionalism on the performance of Banyumas Health Office employees. The population in this study were all employees of the Banyumas Health Office, totaling 145 employees. The sampling technique used a non-probability samp ling method with data collection using purposive sampling with the criteria that employees do not have a leadership position and must have worked at the institution for at least one year. therefore Data were collected through a questionnaire containing Likert scale questions with values from 1 to 5. SmartPLS 3.2.9 was used to analyze the data that had been collected. The results showed that the perceived organizational support variable had an insignificant effect on employee performance, employee engagement had an insignificant effect on employee performance, organizational commitment had no effect on employee performance, and professionalism had a positive and significant effect on employee performance. Keywords: Perceived Organizational Support, Employee Engagement, Organizational Commitment, Performance